Effect of quadriceps muscle strength, range of knee motion and motivation on static body balance in patients post anterior cruciate ligament (acl) reconstruction - Ahmad Syafei; james tangkudung; junaidi (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The purpose of this research is the effect of quadriceps muscle strength, knee range of motion and motivation on static body balance in patients after anterior cruciate ligament (ACL) reconstruction. The target population of the study were all post-ACL reconstruction patients, which consisted of 30 patients at a special clinic for handling sports injuries at Physio IN Bekasi. Static body balance instrument (Y) using the Stork Stand Test. The quadriceps muscle strength instrument (X1) uses a quadriceps muscle strength test with a sphygnomanometer test. Range of motion (ROM) of the knee (X2) using a goniometer. Motivation (X3) uses a motivation test with a questionnaire, the questionnaire test is arranged according to the Likert scale. The result of this research is the direct effect of variable X1 on Y = 12.96%. The direct effect of the X2 variable on Y = 25.2%. The direct effect of the X3 variable on Y = 15.68%. The direct effect of the X1 variable on X3 = 19.8%. The direct effect of variable X2 on X3 = 6.86%. The indirect effect of variable X1 on Y through X3 = 28.75%. The indirect effect of variable X2 on Y through X3 = 36.7%.